PENGEMBANGAN SOFTWARE PEMBELAJARAN BERBASIS VISUAL BASIC PADA MATERI INVERS MATRIKS - Randhi Nanang Darmawan; Lailatul Cahyani (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2017)
This paper consists of Research and Development that focus on making  and building  some programs for mathematics education especially discusses invers of matrix. Invers of matrix in Senior High School was introduced in 3rd class and just explained matrix 2x2 and 3x3 . However, it is not an easy matter/thing to determine invers of matrix  because there are some steps that make some students confused and found some difficulties to do it. Therefore, the researcher offers the following steps: First find determinant of matrix, second matrix cofactor and then transpose matrix cofactor become adjoin of matrix, finally multiply adjoin of matrix with determinant. From those steps, sometimes students miss it, so in this paper we will discuss the development of education software (prototype) to compute and determine invers of some matrix. Research and development methodology is applied in this research. The result of the research is merely a trial product for a senior high school and has been proven to be affective and got good feedback as well as respond from the students.This paper consists of Research and Development that focus on making and building some programs for mathematics education especially discusses invers of matrix. Invers of matrix in Senior High School was introduced in 3rd class and just explained matrix and . However, it is not an easy matter/thing to determine invers of matrix  because there are some steps that make some students confused and found some difficulties to do it. Therefore, the researcher offers the following steps: First find determinant of matrix, second matrix cofactor and then transpose matrix cofactor become adjoin of matrix, finally multiply adjoin of matrix with determinant. From those steps, sometimes students miss it, so in this paper we will discuss the development ofeducation software (prototype) to compute and determine invers of some matrix. Research and development methodology is applied in this research. The result of the research is merely a trial product for a senior high school and has been proven to be affective and got good feedback as well as respond from the students.